EFEKTIVITAS PEMBELAJARAN MENGGUNAKAN MULTIMEDIA INTERAKTIF (ADOBE FLASH CS6) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD N JURUG SEWON - Nur Hidayati (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this research to test the effectiveness of using interactive multimedia learning compared to conventional learning. This research was conducted in SDN Jurug Sewon with all population of fifth grade consists of three classes is 75 students. Samples were taken using cluster random sampling. Data collection technique used documentation and tests techniques. Data were analyzed using descriptive analysis and hypothesis testing using t-test that begins with the analysis prerequisite test including normality test distribution and homogeneity of variance. Results obtained by analysis = 6,418 > = 1,678, that mean, using interactive multimedia had significant effect. Percentage completeness of student learning outcomes experimental group and the control group was 79.17% and 16% with a mean of 78.67 for the experimental group and 56.48 for the control group. In such a way, learning using interactive multimedia was effective for learning outcomes Mathematical fifth grade students of SDN Jurug Sewon.